Universality in size-driven evolution towards bulk polarizability of metals. Issue 37 (18th September 2018) - Jellinek, Julius; Jackson, Koblar A.
Abstract : The size-induced transition to metallicity, as gauged by polarizability-based descriptors, exhibits universal features. Abstract : The properties and characteristics of materials on the subnano/nano scale are very different from those of their bulk counterparts. The evolution of materials properties with size is the holy grail of nanoscience. An intriguing question then is: Can one predict what type of material (metal, semiconductor or insulator) an unidentified element will be, when in bulk quantities, solely from the properties it exhibits over a limited range of the subnano/nano size-regime? We demonstrate here that for nominally metallic elements ( i.e., elements that are metals in bulk quantities) the answer to this question is "yes", and the very identity of the element also can be established. Most importantly, we show that the phenomenon of size-induced transition to metallicity, as gauged by polarizability, is characterized by features and trends that are universal for all metals. Combining numerical simulation data with an analytical model we introduce a universal constant and derive equations that express the universality explicitly.